Shadowed! - Rothenberg, Ellen 1949- (The Green Lantern Press, 2018)
"Shadowed! confronts the slippage of time and action within Ellen Rothenberg’s 2015 Sector 2337 exhibition, elsetime. Sweeping through the studio of Bertolt Brecht, Woodstock in the sixties, Berlin in the nineties, and the Syrian protests of today, Shadowed! projects a dispersive, unfolding temporality. Beginning with a suite of elsetime photographs, the book continues with reflections on the show by Hannah B Higgins, Jeffrey Skoller, Caroline Picard, and Shawn Michelle Smith—spreading out from there into an artist’s archive that includes scanned fragments of writings by Stefan Brecht, Allen Ginsberg, Angela Davis, and transcribed contributions from Simone Forti. A subsequent section includes documentation of performances produced in response to elsetime by artists, activists, and musicians Mark Booth, Alexandria Eregbu, Becky Grajeda,Terri Kapsalis, Tim Kinsella, Anne Elizabeth Moore, and Dao Nguyen. Shadowed! ends with the transcript of a public conversation that took place within the original exhibit, capturing a discussion that incorporates an active audience. By layering these performative, photographic, and written encounters, Shadowed! allows the afterimage of an exhibition to unfurl beyond the gallery, beyond this book, and into its own elsetime"--Back cover
Keywords: Rothenberg, Ellen -- 1949-; Rothenberg, Ellen / 1949- / Elsetime; Rothenberg, Ellen / 1949- / Criticism and interpretation; Art, Modern / Exhibitions / 21st century